Rhizosphere actinobacteria isolated from Pometia pinnata and its antimicrobial activity - ISRA JANATININGRUM; AMELIA ZAHRA; FITRIYANTI FITRIYANTI; VIVI ANGGIA (Society for Indonesian Biodiversity, 2024)
Abstract. Janatiningrum I, Zahra A, Fitriyanti, Anggia V. 2024. Rhizosphere actinobacteria isolated from Pometia pinnata and its antimicrobial activity. Biodiversitas 25: 1007-1014. Actinobacteria are currently the largest antibiotic-producing bacteria due to their extreme environments such as soil, roots and rhizosphere. The diversity of rhizosphere actinobacteria is affected by plant exudates. Pometia pinnata is a plant that has long been used for traditional medicine in Indonesia. This study was aimed at isolating and evaluating isolate and evaluate the actinobacteria rhizosphere of P. pinnata, to screen their antibacterial and antifungal properties. Isolation of actinobacteria was done by using serial dilution method and grown on media. About 34 actinobacteria were successfully isolated from the rhizosphere of P. pinnata and 50% of them showed index antimicrobial activity for Staphylococcus aureus ATCC 6538 (0.52), Streptococcus pneumoniae ATCC 1705 (2.87), and Escherichia coli ATCC 25922 (1.28). Several microbial isolated microbes (20.8%) were found capable in inhibiting fungal growth. The highest antibacterial activity against all bacteria was shown by RM12 isolate. The aqueous fraction of RM12 isolate demonstrated a significant inhibitory activity against S. aureus ATCC 6538 and E. coli ATCC 25922 at concentrations of 250 ppm, 500 ppm and 1000 ppm. TLC bioautography showed that aqueous fraction RM 12 do not belong to the polyphenol or phenol compound group. The RM12 was characterized by using 16S ribosomal RNA sequence found to belong to actinobacteria genera to Streptomyces bungoensis.